Implementation of Learning Models To Improve Elementary School Students' Critical Thinking Abilities - Kustiarini, Kustiarini; Sarwi, Sarwi; Rusilowati, Ani; Dewi, Novi Ratna (Universitas Negeri Semarang, 2024)
Critical thinking ability is one of the core skills that must be developed in elementary school education, considering its importance in forming analytical thinking and effective problem solving. The right learning model can be the key to facilitating the development of students' abilities. This research aims to identify the role of learning models in improving students' critical thinking abilities, by emphasizing the importance of these abilities in the current educational context. The literature review method is used to collect data from various related literature sources. This type of research is analytical descriptive which examines theories about learning and critical thinking. The results of the literature review show that the application of relevant learning models can significantly influence the development of students' critical thinking skills, especially through student-centered learning (Contextual Teaching and Learning (CTL), flipped classroom, and technology-based learning), collaborative learning (jigsaw and integration STEM), and the use of problem solving models (Problem Based Learning (PBL), inquiry-based learning, and project-based learning). The implication of this research is the importance of integrating learning models that support the development of critical thinking in learning design in schools. This research provides a strong theoretical basis for the development of more effective learning strategies in the context of elementary school education. Further research is recommended to empirically test the effectiveness of these learning models in different classroom contexts.